2011
DOI: 10.1039/c0nr00758g
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-loaded biodegradable polymeric micelles for colon cancer therapy in vitro and in vivo

Abstract: Curcumin is an effective and safe anticancer agent, but its hydrophobicity inhibits its clinical application. Nanotechnology provides an effective method to improve the water solubility of hydrophobic drug. In this work, curcumin was encapsulated into monomethoxy poly(ethylene glycol)-poly(ε-caprolactone) (MPEG-PCL) micelles through a single-step nano-precipitation method, creating curcumin-loaded MPEG-PCL (Cur/MPEG-PCL) micelles. These Cur/MPEG-PCL micelles were monodisperse (PDI = 0.097 ± 0.011) with a mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
229
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(246 citation statements)
references
References 58 publications
12
229
2
3
Order By: Relevance
“…The release of MTX/PN-H nanoparticles was a little slower than that of MTX/PN-L nanoparticles. Comparing to other anticancer drug loaded polymeric nanoparticles reported previously [23][24][25][26][27], the release of MTX loaded polyrotaxanes nanoparticles was very fast. There were two reasons to explain this phenomenon, one was that the hydrophilicity of MTX was better than other anticancer drugs such as doxorubicin and 9-nitro-20(S)-camptothecin, which resulted faster diffusion from the nanoparticles to themedium.…”
Section: Resultsmentioning
confidence: 90%
“…The release of MTX/PN-H nanoparticles was a little slower than that of MTX/PN-L nanoparticles. Comparing to other anticancer drug loaded polymeric nanoparticles reported previously [23][24][25][26][27], the release of MTX loaded polyrotaxanes nanoparticles was very fast. There were two reasons to explain this phenomenon, one was that the hydrophilicity of MTX was better than other anticancer drugs such as doxorubicin and 9-nitro-20(S)-camptothecin, which resulted faster diffusion from the nanoparticles to themedium.…”
Section: Resultsmentioning
confidence: 90%
“…Some recently discovered carcinogenic and noncarcinogenic agents such as certain dietary substances, natural hormones and synthetic compounds have been proposed to stop or reverse the process of carcinogenesis to alleviate the limited efficacy and considerable toxicity of conventional chemotherapy (Morse et al, 1993), in which increasing attention has been paid to somatostatin and its analogs that have been reported to exert antineoplastic effects in a wide range of tumor types such as carcinoid, osteosarcoma, leukemia, and cancers of thyroid, breast, lung, liver, pancreas, colon, as well as gastric carcinomas (Scarpignato et al, 2001;Ain et al, 1997;Marschke et al, 1999;Setyono et al, 1987;Shan et al, 2003;Gencosmanoglu et al, 2002;Lee et al, 2002;Giannetti et al, 2000;Yuen et al, 2002;Gou et al, 2011b). Poly(ε-caprolactone) (PCL), biodegradable polyesters, is most commonly used for pharmaceutical applications.…”
Section: Original Articlesmentioning
confidence: 99%
“…Additionally, it has been reported that the zebrafish expressing a truncated form of APC with either retinoic acid or a selective COX-2 inhibitor decreased -catenin in the cell. Curcumin-loaded biodegradable polymeric micelles (Cur/MPEG-PCL) has been shown to efficiently block angiogenesis in transgenic zebrafish model (Gou et al, 2011). Similarly, the incorporation of doxorubicin in MPEG-PCL micelles enhanced the anticancer activity and decreased the systemic toxicity of doxorubicin in Zebrafish and has implications for CRC treatment (Lee et al, 2006).…”
Section: Zebrafish Model In Chemoprevention and Therapymentioning
confidence: 99%